IMPLEMENTATION OF FUZZY TSUKAMOTO LOGIC TO DETERMINE THE NUMBER OF SEEDS KOI FISH IN THE SUKAMANAH CIANJUR FARMER`S GROUP - Deden Farhan; Feri Sulianta (Informatika, Universitas Jenderal Soedirman, 2023)
One of the innovation programs of the Sukamanah Village Karangtengah Cianjur farmer group is in the field of fisheries. One of the programs carried out is the nursery for ornamental Koi fish. Nursery of Koi fish is done because the market demand for Koi fish is high, but there are still very few Koi fish providers. However, farmer groups are currently unable to determine the number of seeds that must be provided to meet market needs to obtain maximum profit. To overcome this, a system is required that can calculate the number of seeds needed based on fish supply and market demand. Fuzzy logic can help humans make decisions; besides, fuzzy logic is an appropriate way to map an input space into an output space. This research aims to build an application using fuzzy logic to determine the number of seeds needed based on the amount of supply and market demand for Koi fish. The data used is sourced from the Sukamanah Farmer’s group, Cianjur. The results showed that using fuzzy logic succeeded in predicting the number of koi fish seeds that must be provided with an accuracy rate of 94,78% using the MAPE method.